Determining Factors Influencing Fertility Stalls in Low and Middle-Income Countries: A Systematic Review (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study investigates the factors driving fertility stall in low and middle-income countries.Design/Methodology/Approach: A systematic literature search was performed to discover relevant research on fertility stalls. Papers published between 2000 and 2024 were considered. Only 16 of the 2380 papers on fertility stalls in poor countries discovered by the University of Gothenburg Library through prominent databases, including CINAHL, GUPEA, JUNO, Mediearkivet, NE.se, PubMed, and Scopus, met the criteria for this study. Content similarity clustering is implemented through Rayyan software based on their similarity ratings.Research Limitations: Countries' classifications are subject to change, and the World Bank index is continually updated. For example, a country classified as low and middle-income in 2000 will be classified as high-income in 2024.Findings: Several factors have been identified as impacting fertility stalls. Fertility stall in low- and middle-income countries was found to be influenced by age at the first union or marriage, women's education, contraceptive use, post-partum infecundity, female labour, fertility preference, family planning initiatives, and child mortality.Practical Implication: The results will inform governments and reproductive health policymakers on how to combat the factors causing fertility delays, especially in developing countries, and develop strategies to eliminate these factors, thereby achieving universal access to reproductive health.Social Implication: Addressing fertility bottlenecks requires a comprehensive approach that incorporates cultural and public health initiatives to promote sustainable population management and gender empowerment.Originality/Value: Little research has been done on the factors that drive fertility stalls in poor countries. The outcomes of this study will contribute to our understanding of the factors causing fertility stalls, thereby increasing access to reproductive health rights.
Keywords: Decline. fertility stall. Rwanda .transition. women